Educational Professionals’ Decision Making for Professional Growth using a Case of Twitter Adoption - Tucker, Lauren (TechTrends, 2019)
This paper is a report of an examination of educational professionals’ perspectives on their decision processes to use a Twitter personal learning network (PLN). When investigating each of the participants’ decision-making processes to accept or reject the use of a Twitter PLN, the externally supported individualized learning experience was integral to the educational professionals’ active decision to adopt the new tool. The five major findings revealed external stimulus and support is (1) vital to address pre-existing attitudes and beliefs, (2) to target the acquisition of technical and implementation knowledge, and (3) to encourage continued exposure, interaction, and exploration. The final two findings focus on the (4) interaction with a social learning community supports decision making and informal learning, and (5) personal experimentation and exploration of a Twitter PLN allows educational professionals to build their professional network, quickly access high quality information, and read educational material. Educational professionals’ informal learning activities were also revealed while using their PLN. Educational professionals reported sharing information and resources with colleagues as having the most significant impact on professional practice. In addition to interviews, the nature of the Twitter platform provided valuable evidence of informal learning activities. These activities reflected in the educational professionals’ tweets included: reading educational subject matter, reflection and collaboration. Also, a new category: Resource Collection was created to reflect the second most popular activity on educational professionals’ Twitter PLN.
Keywords: Decision Making; Digital Education and Educational Technology; Informal Learning; Personal Learning Network (PLN); Professional Growth; Social Media; Twitter; dept.sed

College Access, Success and Equity for Students on the Autism Spectrum. - Accardo, Amy L; Bean, Kimberly; Cook, Barbara; Gillies, Ann; Edgington, Rebecca; Kuder, S Jay; Bomgardner, Estyr M (Journal of autism and developmental disorders, 2019)
College may be considered a gateway to success, yet access to college is limited for young adults with autism. Given the research recommendations to elicit student experiences and to communicate among universities to improve college access, success, and equity, the present study examined the questions: What factors are perceived as pathways to success or barriers to success by college students on the autism spectrum? What university provided accommodations and/or support services do they prefer? Participants from four universities completed surveys and semi-structured interviews. Findings from the multi-university study suggest the need to provide transition planning and systematic non-academic social and emotional supports from the start of the college experience as well as specific training for faculty, staff, and peers.
Keywords: *Academic Success; *Autism Spectrum Disorder/rh [Rehabilitation]; *Mainstreaming, Education/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Academic Success; Accommodations; Adolescent; Article; Autism Spectrum Disorder; Autism Spectrum Disorder/px [Psychology]; Autism spectrum disorder; College; Female; Humans; Mainstreaming, Education; Male; Mental health; Students; Students/px [Psychology]; Students/sn [Statistics & Numerical Data]; Universities; University; Young Adult; academic success; adolescent; adult; autism; college; college student; dept.cmd; dept.sed; disability; executive function; female; financial management; follow up; health equity; human; longitudinal study; male; mental health care; motivation; peer-reviewed; priority journal; psychology; self concept; semi structured interview; social network; social support; student; student attitude; university; young adult

What's a middle school teacher to do? Five evidence-based practices to support English learners and students with learning disabilities - Hovey, Katrina A.; Miller, Rhonda D.; Kiru, Elisheba W.; Gerzel-Short, Lydia; Wei, Yan; Kelly, Jerae (Preventing School Failure: Alternative Education for Children and Youth, 2019)
General education teachers are challenged with meeting the unique instructional needs of every learner in their classrooms, which increasingly include English learners (ELs) and students with learning disabilities (LD). This article uses vignettes to demonstrate how a middle school content teacher uses five strategies: building prior knowledge, building vocabulary, explicit instruction, visual representation, and opportunities to respond to support his students. Each strategy is evidence based for ELs and for students who have an identified LD. Research supports that ELs and students with LD benefit from specific instructional strategies that enhance the accessibility of course content and potentially improve learning outcomes. © 2019, © 2019 Taylor & Francis Group, LLC.
Keywords: English learners; dept.rdg; dept.sed; evidence-based strategies; instructional practices; learning disabilities; peer-reviewed

Teachers' academic training for literacy instruction - Oliveira, Celia; Lopes, Joao; Spear-Swerling, Louise (European Journal of Teacher Education, 2019)
Literacy instruction is a powerful determinant of children's academic and school outcomes. Teachers' training for literacy instruction is therefore critical for children's reading learning. The present study examined the contents of 130 courses related to literacy instruction from a representative national sample of primary teachers' undergraduate programs (N =81), to address the following issues: which courses, related to literacy instruction, are included in the curriculum of undergraduate training programs? Which is the weight of the courses in undergraduate programs? What are the contents of the courses? The results show that most critical features of literacy instruction are included in the course contents of most programs (e.g. phonics, theory of literature). Still, some other critical features are underrepresented (reading/writing comprehension skills) or apparently missing (assessment and intervention in reading/writing problems). Moreover, the time allocated to literacy instruction seems to be scarce. Still, wide differences across university programs and courses were found.
Keywords: Literacy instruction; dept.sed; peer-reviewed; reading and writing; specific content knowledge; undergraduate teachers' training; undergraduate teachers’ training

Engaging culturally and linguistically diverse families of children with disabilities - Gerzel-Short, Lydia; Kiru, Elisheba W.; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan; Miller, Rhonda D. (Intervention in School and Clinic, 2019)
Classrooms are increasingly more diverse, and student success can be enhanced through family engagement, especially for culturally and linguistically diverse (CLD) students with disabilities. Too often teachers are stymied by how to engage CLD families of children with disabilities. Common practices of parent involvement are ineffective and fail to appreciate families as members of the educational team. Family engagement seeks to establish and maintain authentic family-school partnerships based on mutual respect and shared agency for student academic and social success. This column provides specific family engagement strategies that teachers and schools can implement in an effort to provide reciprocal collaboration.
Keywords: cultural and linguistic diversity; dept.rdg; dept.sed; disabilities; diverse families; family engagement; family-school collaboration; multicultural; peer-reviewed

The challenges of recruiting and retaining dual language teachers - Howard, Elizabeth; López-Velásquez, Angela M. (Dual language education: teaching and leading in two languages, 2019)
Across the United States, the popularity of dual language education (DLE) has grown considerably over the past several decades, but finding qualified bilingual teachers to staff these programs is an ongoing issue for administrators. Using the Guiding Principles for Dual Language Education as a framework, this chapter addresses this urgent issue by exploring dual language teacher recruitment and retention through the experiences and recommendations of teachers and administrators in Connecticut. Findings address participants’ perceptions of teacher recruitment and retention, staff selection, workplace climate, and staff evaluation. Cross-cutting themes include the value of shared responsibility and shared decision-making in addressing this complex issue, the need for creativity and flexibility to increase pathways to certification for dual language teachers, and the importance of positive working conditions.
Keywords: Alternative routes to certification; Bilingual teachers; Dual language; School climate; School-university partnerships; Teacher certification; Teacher recruitment; Teacher retention; Teacher shortage; dept.sed